2015
DOI: 10.5901/mjss.2015.v6n3s2p353
|View full text |Cite
|
Sign up to set email alerts
|

Describing the Need for Affordable Livable Sustainable Housing Based on Maslow’s Theory of Need

Abstract: Housing plays an important role in people 's wellbeing, contributing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Parris and Kates' (2003) discussion of the requirement to satisfy basic human needs as part of a sustainability transition identifies hunger, equality, health, and education as basic needs to be satisfied, consistent with Maslow's theory [10]. Baqutayan et al (2011) examined on how certain standards need to be encountered in housing for the societal wellbeing and then defined the need for affordable livable sustainable housing based on Maslow's theory [11]. Walsh (2010) believed that applying Maslow's theory to the examination of global sustainability has its merit [12].…”
Section: Sustainable Development and Maslow's Hierarchy Of Needs Theorymentioning
confidence: 91%
“…Parris and Kates' (2003) discussion of the requirement to satisfy basic human needs as part of a sustainability transition identifies hunger, equality, health, and education as basic needs to be satisfied, consistent with Maslow's theory [10]. Baqutayan et al (2011) examined on how certain standards need to be encountered in housing for the societal wellbeing and then defined the need for affordable livable sustainable housing based on Maslow's theory [11]. Walsh (2010) believed that applying Maslow's theory to the examination of global sustainability has its merit [12].…”
Section: Sustainable Development and Maslow's Hierarchy Of Needs Theorymentioning
confidence: 91%
“…Black people represent 13 percent of the U.S. population, and yet only 8.9 percent of homeowners are Black (Perry et al 2020). Access to safe and affordable housing is an integral component of well-being since it decreases the risk of homelessness among vulnerable populations, increases a household's ability to manage financial obligations and crises, provides stable learning environments, and improves both educational and health outcomes (Brisson 2014;Schwartz 2016;Baqutayan et al 2015Baqutayan et al , 2016. Moreover, property ownership and access to affordable and stable housing, such as through homeownership, represent major wealth-building mechanisms (Ray et al 2021;Hanks et al 2018;Asante-Muhammed et al 2016;Solomon et al 2019a).…”
Section: Ecological Imperialism and Stratification Economics Housing ...mentioning
confidence: 99%
“…The criteria of decent and quality housing, which is a decent house that ensures security, provides easy access to employment and other service facilities and selfselected low cost environments [3]. The survey also revealed that almost all of its correspondents wanted a sustainable dwelling where sustainable means that people want to continue living with the same community in the same place for now and in the future "people / neighbors continuing to want to live in the same community, both now and in the future."…”
Section: Issue and Design Contextmentioning
confidence: 99%